Steroids Therapy in Patients With Severe COVID-19: Association With Decreasing of Pneumonia Fibrotic Tissue Volume - He, Jin-wei; Su, Ying; Qiu, Ze-song; Wu, Jiang-jie; Chen, Jun; Luo, Zhe; Zhang, Yuyao (Frontiers in Medicine, 2022)
Steroid therapy has been applied in pneumonia treating for a long time. It has shown positive efficacy during the treatment of SARS and MERS. However, since the absence of specific evidence to systematically expound its effect, the steroids’ use in pneumonia is still controversial. We use longitudinal chest CT images to monitor the pulmonary lesion evolution, and aim to study the effect of steroids therapy in the COVID-19 pneumonia caused pulmonary lesion progression. We retrospectively enrolled a number of 78 patients with severe to critical COVID-19 pneumonia, among which, 25 patients (32.1%) received steroids therapy. Based on clinical symptoms, patients were further divided into two groups with severe illness and significant-severe illness. Serial longitudinal chest CT scans were performed for each patient. Lung tissue was segmented into 5 lung lobes and mapped into 5 pulmonary tissue type categories based on their Hounsfield unit value. The volume changes of normal tissue and pneumonia fibrotic tissue in the entire lung and each 5 lung lobes were the primary outcomes. In this study, we calculated the changing percentage of tissue volume relative to its baseline value to directly demonstrate the disease progress. We found that steroid therapy was associated with the decrease of pneumonia fibrotic tissue (PFT) volume proportion and its effect was related to the disease severity. For example, after 4 CT cycles treatment (about 25-30 days), the volume reduction percentage of PFT in entire lung was -59.79[12.4]% for the steroid-treated patients with severe illness, and its p-value was 0.000 comparing to that (-27.54[85.81]%) in non-steroid-treated ones. But for the patient with significant-severe illness, PFT reduction in steroid-treated patients was -41.92[52.26]%, showing a 0.275 p-value comparing to -37.18 [76.49]% in non-steroid-treated ones. The PFT evolution analysis in different lung lobes indicated consistent findings as well.